Transformational leadership: a qualitative study from waqf institutions in malaysia - Jasni, Jabran; Sharip, Sharfizie Mohd; Daud, Dalila; Ibrahim, Sara; Kamdari, Azurah (IJISH (International Journal of Islamic Studies and Humanities), 2023)
This study entails an exploratory investigation of transformative leadership in the context of waqf institutions. In analysing the transformational leadership style, the study interviewed the heads of the State Islamic Religious Councils in charge of waqf institutions in Malaysia. The best practices in the two waqf institutions were found to fall under four areas related to transformational leadership: idealised influence, inspirational motivation, intellectual stimulation, and individualised consideration. The four categories were generated from three sub-categories, bringing the overall total to 12 sub-categories. The findings demonstrate the applicability of transformational leadership in waqf institutions, where it fosters employee inspiration, contentment, and creativity. In addition, this study adds to the body of knowledge as there are not many previous investigations on transformational leadership in the setting of waqf institutions. Waqf sector leaders can use this study’s practical application to comprehend, apply, practice and evaluate transformational leadership in accomplishing the objectives of their respective waqf institutions.